Physical and Chemical Properties of Soils in Gambari Forest Reserve Near Ibadan, South Western Nigeria. - Akintola O. Opeyemi; Bodede Idayat Adewunmi; Abiola Isaac Oluwaseyi (Journal of Bioresource Management, 2020)
The different features of soil greatly affect the flora and vegetative diversity of a forest. The physical and chemical characteristics of soils in Onigambari Forest Reserve were evaluated to assess the fertility and productivity status of the soils. Fifteen soil samples collected from different sample locations were analyzed for soil texture (sand, silt and clay), bulk density, porosity, pH, organic matter, total nitrogen, available phosphorus, exchangeable bases (Na, K, Ca and Mg) and available micronutrients (Zn, Cu, Fe and Mn). Texturally, the studied soils were loamy sand and sandy loam with percentage of sands (71.2-84.2 %), silts (7.4-10.4 %) and clay (6.4-19.4 %). The bulk density of the soils was 1.61-1.83 % while the porosity of the soils ranged from 35.2-44.1 %. The slightly acidic to neutral soil pH (5.90 - 6.60) and medium organic matter content (1.68 -2.60 %) suggest adequate level of soil nutrients. The soils had high total nitrogen (0.35 -0.65 %) and available phosphorus contents between 10.98 and 18.22mg/kg.